Pelaksanaan Tata Tertib Sekolah Oleh Siswa Di SMP Negeri Kota Banda Aceh - Muntazir Muntazir; M Husen; Nurbaity Bustamam (JIMBK: Jurnal Ilmiah Mahasiswa Bimbingan & Konseling, 2017)
ABSTRACT This study aims to describe the implementation of school rules and obstacles faced by students in running the school order in public junior secondary school in Banda Aceh. The method of this research is descriptive with the mixed approach. The location of this research is located in three public junior secondary schools namely SMP Negeri 1 Banda Aceh, SMP Negeri 4 Banda Aceh, and SMP Negeri 18 Banda Aceh with a population of second and third-grade students as many as 1046 students. Sampling is calculated using Slovin formula with α = 5% that is 289. The data collection is done by using questionnaire of Likert scale model and interview. Data analysis used quantitative and qualitative descriptive analysis. The result of the research indicates that almost all students admitted that they have implemented good school rules, namely the percentage of excellent category as much as 73.9% and the percentage of good category as much as 25.7%. The tendency of good disciplinary execution is also seen in each item. However, in some cases, there are still violations that are recognized by the students. While the obstacles faced by students in implementing this school order comes from internal factors such as self-regulation and external factors in the form of family and teacher stimulants in schools.Keywords: Implementation, Constraints, Code of Conduct, students, Junior High School